Penyuluhan Kebersihan Diri Dan Pendampingan Pembiasaan Pola Hidup Bersih Sehat (Pbhs) Serta Penanggulangan Skabies Pada Santri Pondok Pesantren Darul Hijrah Putra Martapura - Rifqoh, Rifqoh; Insana, Aima; Rizani, Khairir (UPPM Poltekkes Kemenkes Banjarmasin, 2022)
Scabies is a skin disease caused by Sarcoptes scabiei mite. Scabies is transmitted through direct or indirect physical contact regardless of socioeconomic status, gender, or age, especially in Islamic boarding schools. The high prevalence of scabies is caused by less personal hygiene and environmental sanitation dan Clean Healthy Lifestyle (PHBS) behavior. This PKM aims to improve knowledge, personal hygiene, environmental sanitation, and PHBS behavior in preventing scabies in Darul Hijrah Putra Martapura (DHP) Islamic Boarding School students. The implementation method was counseling, questionnaires, observation, early detection of scabies, treatment, and assistance in habituating PHBS for 3weeks to 53students of DHP. The results of microscopic examination with adhesive tape method showed 9(16.98%) students were positive for scabies, 6(11.32%) of them had mild symptoms and 3(5.66%) students had severe symptoms. The treatment was carried out for the positive scabies students. The results of evaluation after this PKM are scabies students have recovered, there is an increase in knowledge to 100% good after counseling, PHBS habituation results in the booklet and 52(99%) students increase in PHBS behavior scores, personal hygiene increases to a good category 45(84.91%) students. And the category is not good, with only 8(15.06%) students and the sanitation of the dormitory environment is quite good, except for the occupancy density, that 36m2 rooms occupied by 16 students (standard 1 person/9m2). There is an improvement in facilities and infrastructure. It is recommended to partners continue PHBS habituation assistance and carry out early detection on prospective students before enter DHP boarding schools.